Immunological properties of glycolipids from membranes of Acholeplasma laidlawii. - Ryan, M D (1975)
Glycolipids, the predominant class of lipids in the membranes of Acholeplasma laidlawii, are the haptenic determinants that react with anti-A. Laidlawii serum to fix complement. The predominant complement-fixing activity of the membrane glycolipids was associated with the monoglucoysyl diglyceride, diglucosyl diglyceride, glycerlphosphoryl diglucosyl diglyceride (GPDD), and an unknown lipid B, which did not react with ninhydrin but release glucose and glycerol and traces of phosphorus upon hydrolysis. The glycolipids monoglucosyl diglyceride and diglucosyl diglyceride or GPDD and unknown lipid B were paired as a result of their cross-reactions with selective antisera prepared with the aid of reconstituted membrane complexes containing membrane lipids. Reconstituted membrane complexes assembled from [14C]monoglucosyl diglyceride and delipidated membrane proteins gave optimal complement fixation titers before saturation of the complexes with the ]14C]monoglucosyl diglyceride. The phosphoglycolipid of the membrane, GPDD, was anticomplementary as a pure lipid, a cholesterol liposome, and a reconstituted membrane complex. This anticomplementary activity, which was caused by 3 mug of pure GPDD, affected both human and guinea pig complement. Although human C1, C4, C3, and C5 were not inhibited by GPDD, C2 was inhibited 10-fold by reconstituted membrane complexes containing 150 mug of GPDD. A role for this phosphoglycolipid is discussed in the hypothetical mechanism of inhibition of C2 attachment to SAC1, 4 sites.